The ISCAP in the Shadow of the Russian-Ukrainian War - Pintér, Tibor (Journal of Central and Eastern European African Studies, 2024)
After the shock of the coronavirus, the world was hit by another blow: the Russian-Ukrainian war. This had a number of effects on the world, causing inflation and an energy price explosion. In the case of Africa, even food security was at risk due to the decline in Russian and Ukrainian grain. However, what is chaos for the world is an opportunity for jihadist movements to gain strength, as the burden on citizens increases social discontent. The situation in sub-Saharan East Africa is no different. The Islamic State's youngest province, ISCAP (Islamic State of Central Africa Province), created in 2019, remains dangerous, although the jihadist movements that make it up are not achieving the spectacular successes of the past. The Allied Democratic Forces (ADF) is based in the Congo-Uganda border region, while al-Shabaab in Mozambique has emerged in the northern province of Cabo Delgado. Their exact links to the Islamic State are not fully known, but recent reports suggest that the Islamic State of Somalia may be a center of back-and-forth communication between the two parties. The study focuses on ISCAP and the period since the Russian-Ukrainian war. In other words, what trends can be observed, how dangerous they could be and, most importantly, what opportunities they face and what kind of response is coming from the security forces. For the status of jihadist organisations, I refer to Stig Jarle Hansen's book Horn, Sahel and Rift, published in 2019. For the others, I rely on reports, analyses and, above all, recent news that may bring about changes in the way things have been done so far, one example being the LNG project being built in Cabo Delgado.